Sectoral Analysis of e-Banking Industry – An Evolutionary Approach - Seranmadevi, R.; Latha Natarajan, M.; Saravanaraj, M. G. (Indian Journal of Finance, 2011)
This article clearly examines what types of e-Banking credit card technologies are open to customers in India. It then proceeds to examine how various e- Banking might be attractive to potential customers in terms of improved accessibility, affordability and ease of use. It also focuses on the functionality of electronic credit cards, frequency of usage, mode of repayment, value addition facilities offered along with the credit cards for different client groups. This article describes how the evolution of the credit card should support in improvement of standard of living, adequate awareness and literacy levels of using the credit cards by the various segments of customers.